PET/CT of Duodenal Gangliocytic Paraganglioma. (May 2020) - Morland, David; Dejust, Sébastien; Brasseur, Mathilde; Monnier, Louise; Papathanassiou, Dimitri
Abstract : Abstract: An 87-year-old woman with leg-type lymphoma underwent a staging 18 F-FDG PET/CT, which demonstrated besides leg lymphomatous lesions a round, well-defined, preduodenal mass with moderate FDG uptake. This mass remained unchanged after chemotherapy treatment completion, despite a complete metabolic response of lymphomatous lesions. A biopsy revealed a gangliocytic paraganglioma. Subsequent 18 F-FDOPA PET/CT and somatostatin receptor scintigraphy were positive and did not depict any other lesions.